Tools for Resilience Building and Adaptive Spatial Governance: Instrumente zur Förderung von Resilienz und adaptiver räumlicher Governance - Birkmann, Jörn; Bach, Claudia; Vollmer, Maike (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
Climate change, resilience building and vulnerability reduction are emerging issues in spatial development and spatial planning in Germany, the European Union and globally. This paper introduces different concepts of and views on adaptation, vulnerability and resilience and outlines their implications for spatial planning in the context of a changing climate. On the basis of a conceptual discussion of key terms, the authors underscore the importance of assessing vulnerability as baseline information for the promotion of resilience and the enhancing of adaptation. The challenges of identifying and assessing vulnerability are illustrated through a case study of local flood vulnerability in Cologne with a specific focus on the vulnerability of different population groups as well as critical infrastructures. The respective key elements and phases of such assessments are identified. New challenges with regard to systemic risks are addressed and recommendations for improved linkages between spatial planning and civil protection formulated. The final part of the paper evaluates the upcoming challenges for adaptive planning in the context of climate change adaptation, for example regarding scenario development and its application.